Implementasi Customer Service BRI Dengan Pemanfaatan News Media (Instagram) Untuk Meningkatkan Kepuasan Nasabah Dalam Masa Pandemi Covid 19 - Eki Chandra Nur Iman; Adibah Natasya (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2022)
The purpose of this study was to determine the application of BRI customer service by utilizing news media (Instagram) to increase customer satisfaction during the Covid-19 pandemic. The research approach used in this study is a quantitative approach. This research was conducted at Bank BRI. The sampling technique of this research is random sampling. Respondents in this study were 100 people who are customers of Bank BRI. The data analysis used a structural approach to the Equation Model (SEM) assisted by the smart PLS application. The results of this study are that customer service has a significant positive effect on customer satisfaction, customer service can increase engagement on social media/news media, Instagram news media has a significant positive effect on customer satisfaction.